Explorando o planeta vermelho: atividades didáticas de comparação de aspectos geográficos entre os planetas Terra e Marte - Neves, Tercia de Karla Moreira (2016)
Mars is one of the terrestrial planets that compose the Solar System and from ancient times has aroused curiosity. With the advent of technology focused on studies of celestial bodies, Mars has been the subject of increasing interest. Probes and satellites are regularly sent for monitoring, collection and analysis of data. The properties of the Earth are the key parameters in comparison with other planets. The comparative study is a way to confront similar and disparate phenomena, besides enabling the production of new knowledge and help in the consolidation of the older ones. In this study, we carried out six adapted or unpublished activities in lectures and practices classes in high school involving themes related to cartography, relief modeling and the atmosphere of mars in comparison with physical geographic parameters. In the total, 130 students did the activities. Such activities have shown that some scientific practices can be universalized and used in the process of understanding the geographical space, even outside the planet earth. Due to the impossibility of being in place, it was shown how the technology assists in the analysis of these areas using satellite images and probes equipped with sensors each time more accurate. Also, the activities were designed to contribute to scientific literacy process for students in which the didactic sequence take them to develop skills and competencies to encourage them to develop strategies when faced with new challenges, but also to sense critical of research capacity and identify wrong scientific conceptions and misused.